Direct and indirect coupling mechanisms in a chiral plasmonic system. (13th September 2016) - Wang, Yongkai; Wen, Xiaojing; Qu, Yu; Fu, Tong; Zhang, Zhongyue
Abstract: Artificial chiral plasmonic nanostructures (ACPNs) are widely studied and used in biological monitoring, analytical chemistry, and negative-refractive-index media. The mechanism of direct coupling between two twist metal nanorods has been obtained in usual ACPNs. In this work, we proposed a nanosystem of twist nanorods separated by a metal film (TNMF). By analyzing the charge distributions, a new indirect coupling mechanism is found. According to the equivalent LC resonant circuits, gold nanorods on the two sides of the gold film can be regarded as a receiver and an emitter. These components enhanced transmittance and provided direct and indirect coupling mechanisms for the circular dichroism (CD). The direct coupling mode cannot be explained by impedance matching and can be tuned monotonously by monotonously varying geometric dimensions. However, the CD signal of indirect coupling can be explained by impedance matching and can be tuned to its maximum by varying geometric dimensions when the impedances of both sides of the gold film match. These results can help design novel chiral optical structures and promote combined applications between photons and electrons when a gold film is powered on.